2018
DOI: 10.1097/ta.0000000000001765
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic changes following valproic acid treatment promote neurogenesis and minimize secondary brain injury

Abstract: Administration of VPA attenuated brain lesion size, reduced brain edema, and induced significant changes in the transcriptome of injured brain within 6 hours. Patterns of differential expression were consistent with the proposed neurogenic and prosurvival effects of VPA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Acetylated histone proteins exert their neuroprotective effects by reducing inflammation and inhibiting neuronal cell death (Zou and Crews, 2014 ; Wang et al, 2015 ; Bai et al, 2017 ), which improves neurological functions in many neurological diseases such as cerebral ischemia (Suda et al, 2015 ) and spinal cord injury (Chu et al, 2015 ). Studies from Nikolian et al ( 2017 , 2018 ) have shown that treatment with VPA can upregulate the expression of genes involved in cell survival and proliferation, and improves neurological function in preclinical models of TBI. However, the role of VPA in TBI, and whether treatment with VPA can improve antioxidative effects following TBI, still needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylated histone proteins exert their neuroprotective effects by reducing inflammation and inhibiting neuronal cell death (Zou and Crews, 2014 ; Wang et al, 2015 ; Bai et al, 2017 ), which improves neurological functions in many neurological diseases such as cerebral ischemia (Suda et al, 2015 ) and spinal cord injury (Chu et al, 2015 ). Studies from Nikolian et al ( 2017 , 2018 ) have shown that treatment with VPA can upregulate the expression of genes involved in cell survival and proliferation, and improves neurological function in preclinical models of TBI. However, the role of VPA in TBI, and whether treatment with VPA can improve antioxidative effects following TBI, still needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the penumbra region (adjacent to the site of injury) from the swine subjected to TBI and HS revealed similar trends . Using RNA sequencing, and analyzing the results using Ingenuity Pathway Analysis, we demonstrated that VPA administration was associated with upregulation of an inter‐connected subnetwork of 257 genes that mediates neurogenesis, neurotransmission, and neuro‐regulation ( Figure ).…”
Section: Vpa Decreases the Genomic And Transcriptomic Changes Followimentioning
confidence: 79%
“…( p = 1 × 10 −27 ; Fishers exact test). Reproduced with permission . Copyright 2018, American Association for the Surgery of Trauma.…”
Section: Vpa Decreases the Genomic And Transcriptomic Changes Followimentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that 1) the majority of single nucleotide polymorphisms (SNPs) associated with human disease risk and drug response variability in genomewide association studies (GWAS) are located within noncoding enhancers that regulate gene expression (Maurano et al, 2012;Higgins et al, 2015a;Onengut-Gumuscu et al, 2015); 2) the threedimensional (3D) spatial environment of the neuronal genome is organized such that regulatory gene networks consist of enhancer-gene promoter chromatin loops located within topologically associated domains (TADs) (Rao et al, 2014;Matharu and Ahituv, 2015;Dekker and Mirny, 2016;Guo et al, 2017;de la Torre-Ubieta et al, 2018); and 3) mutations within genes that encode chromatin remodeling complexes and master transcription factors that drive the reprogramming of cell fate mediated by the regulatory epigenome are important determinants of etiology in human neurologic disease (Pohodich and Zoghbi, 2015;Berson et al, 2017;Li et al, 2017;Rajarajan et al, 2018). Furthermore, many psychotropic drugs, including antidepressants and antiepileptics such as valproic acid, act, in part, through induction of neurogenesis and neural developmental mechanisms (Chu et al, 2015;Miller and Hen, 2015;Walker et al, 2015;Nikolian et al, 2018).…”
Section: Introductionmentioning
confidence: 99%